The barriers of home environments for obesity prevention in Indonesian adolescents - Fransisca Handy Agung; Rini Sekartini; Nani Cahyani Sudarsono; Aryono Hendarto; Meita Dhamayanti; Retno Asti Werdhani; Susan M. Sawyer (BMC, 2022)
Abstract Background Obesity and its related cardiovascular-metabolic diseases are growing public health concerns. Despite global attention to obesity, its prevalence is steeply increasing in developing countries, especially in children and adolescents. Eating behaviours and physical activity are modifiable risk factors for obesity that can variably be shaped by families. Eating behaviours and physical activity are especially important during adolescence, given its significance as a foundational period for developing healthy lifestyles. This qualitative study aimed to explore barriers and opportunities around creating healthy lifestyles among adolescents in Indonesia, focussing on family environments from diverse socio-demographic backgrounds. Method In-depth interviews using a semi-structured guide were undertaken with consecutively recruited 10-18-year-old adolescents with overweight or obesity, and their parents, from three different sites: urban (Jakarta, the capital city of Indonesia), peri-urban (West Java Province) and rural (Banten Province). Thematic analysis was used to identify patterns of meaning. Results Nineteen dyads were interviewed. Thematic analysis revealed four themes: limited knowledge of healthy lifestyles; healthy lifestyles not a concern of daily life; limited parenting skills, including inequity around gender roles; and aspects of availability and accessibility. These interconnected barriers influenced lifestyle practices at home within the context of daily preferences and decisions around food and activities. Gender role inequity and healthy food accessibility were more prominent in rural families than in those from urban or peri-urban settings. Conclusions Healthy lifestyles in adolescence may be supported by strategies to enhance parenting skills, build individual motivation, and support the development of more enabling environments.